Adverse donor reaction during and after plateletpheresis in a tertiary care centre - Khajuria, Kajal; Sawhney, Vijay; Sharma, Raman; Gupta, Sonia (International Journal of Research in Medical Sciences, 2017)
Background: Plateletpheresis is the process of collecting platelets, a component of blood involved in blood clotting. The term specifically refers to the method of collecting the platelets, which is performed by a device used in blood donation that separate the platelets and return other portion of blood to the donor. Platelet transfusion can be a life-saving procedure in preventing and treating serious complications from bleeding and haemorrhage in patients having disorders manifesting as thrombocytopenia like in dengue patients, ITP, aplastic anemia, and patients undergoing chemotherapy for leukaemia. In this study, our goal was to retrospectively analyse the adverse reactions occurred during and immediately after plateletpheresis donations. Methods: From January 2015 to October 2016, a total of 66 plateletpheresis procedures were performed in department of transfusion medicine, GMC Jammu, Jammu and Kashmir, India which is a tertiary care hospital. Results: Total 66 procedures were performed during our study period from which, four (6.06%) adverse events were recorded. Out of these four, two (50%) donors suffered from tingling sensation, one (25%) suffered from nausea and vomiting and One (25%) from haematoma formation. Conclusions: In Conclusion, the result of our 22-month study survey document that apheresis procedures performed on cell separators are safe procedures with the low incidence of adverse reactions.